Estrategias de metacognición en la comprensión lectora en la niñez de quinto año de educación general básica en la Escuela General Miguel Rivadeneira Emilio Terán de la parroquia Mulliquindil Santa Ana del cantón Salcedo, provincia de Cotopaxi en el periodo lectivo 2014-2015 - Muso Lema, Edwin Orlando (2015)
This work is based on the general objective of "Design Strategies of Metacognition in reading comprehension of children in fifth grade General Education Basic School of General Teran Emilio Miguel Rivadeneira" due to lack of teaching knowledge of the strategies of metacognition in reading comprehension. The methods used were: inductive analysis and interpretation and formulation of conclusions and deductive in the review of the framework to go from the general to the particular. The results of the research are: difficulties in metacognitive strategies of motivation to perform the task, evaluation, control, physical environment, time control of negative attitudes, have difficulty understanding written texts, relating to the types and processes of reading related skill. It is concluded that reading comprehension is linked to metacognition strategies, the higher the better reading comprehension metacognitive capacity, the lower the metacognitive capacity greater difficulties in reading. This research proposal is to establish strategies to develop metacognitive skills, considering the playful children's interests, to reflect on the ability of self-assessment and awareness of how to develop their own reading processes.